2018
DOI: 10.3390/molecules23061420
|View full text |Cite
|
Sign up to set email alerts
|

Novel Thiazolidinone/Thiazolo[3,2-a]Benzimidazolone-Isatin Conjugates as Apoptotic Anti-proliferative Agents Towards Breast Cancer: One-Pot Synthesis and In Vitro Biological Evaluation

Abstract: In connection with our research program on the development of new isatin-based anticancer candidates, herein we report the synthesis of two novel series of thiazolidinone-isatin conjugates (4a–n) and thiazolo[3,2-a]benzimidazolone-isatin conjugates (7a–d), and in vitro evaluation of their antiproliferative activity towards two breast cancer cell lines; triple negative MDA-MB-231, and MCF-7. Compounds 4m and 7b emerged as the most active congeners against MDA-MB-231 cells (IC50 = 7.6 ± 0.5 and 13.2 ± 1.1 µM, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…Apoptosis study. The levels of the apoptotic markers caspase-3, caspase-9, p53 and Bax, as well as the anti-apoptotic marker Bcl-2 were evaluated by the use of ELISA colorimetric kits per the manufacturer's instructions, as reported earlier 28,29 . Furthermore, the pro-apoptotic potential of spirooxindole 6a towards HepG2 cells was assessed using FITC Annexin V Apoptosis Detection Kit by flow cytometry, according to the manufacturer's protocol and referring to the reported procedures 30,31 .…”
Section: Biological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis study. The levels of the apoptotic markers caspase-3, caspase-9, p53 and Bax, as well as the anti-apoptotic marker Bcl-2 were evaluated by the use of ELISA colorimetric kits per the manufacturer's instructions, as reported earlier 28,29 . Furthermore, the pro-apoptotic potential of spirooxindole 6a towards HepG2 cells was assessed using FITC Annexin V Apoptosis Detection Kit by flow cytometry, according to the manufacturer's protocol and referring to the reported procedures 30,31 .…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Furthermore, spirooxindoles 6 h, 6k and 6n-6p displayed moderate antiradical activity with IC 50 values of 46. 29 Ferric reducing antioxidant power (FRAP). FRAP assay is a widely used antioxidant assay that uses antioxidant substances as reducing agents in a redox-linked colorimetric reaction, wherein Fe 3þ is reduced to Fe 2þ at acidic pH that results in a formation of a coloured ferrous-probe complex from a colourless ferric-probe complex 35 .…”
Section: Biological Evaluationmentioning
confidence: 99%
“…The influence of bis-indoles 7e and 9a on cell cycle progression was examined in breast cancer MCF-7 cells, after 24 h of treatment, through DNA flow cytometric assay by the use of BD FACS Caliber flow cytometer, as described previously [27]. The cell cycle distributions were calculated using CellQuest software (Becton Dickinson).…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…The apoptotic action of bis-indoles 7e and 9a was further explored through the investigation of their effect on the phosphatidylserine externalization in breast cancer MCF-7 cells, using Annexin-V-FITC Apoptosis Detection Kit according to manufacturer's protocol, as reported earlier [27].…”
Section: Annexin V-fitc/pi Apoptosis Assaymentioning
confidence: 99%
“…It is thought that conjugating two or more pharmacophoric subunits from different biologically active molecules in the molecular architecture of a single hybrid compound might reduce the risk of drug-drug interactions, overcome the drug resistance, and enhance the biological activity via the potential interaction with two targets as one single entity [31]. In this field, our research group has reported many studies concerning the development of efficient oxindole-based anticancer hybrids (hybrids I-III [32][33][34], Figure 1) that exhibited different enzymatic and cellular targets such as apoptosis induction in different human cancer cell lines [35,36], inhibition of cancer-related carbonic anhydrase IX isoform [37,38], in addition to inhibition of tyrosine kinases [39,40].…”
Section: Introductionmentioning
confidence: 99%